Preparation and properties of flame-retardant neutron shielding material based on EVA polymer reinforced by radiation modification. (September 2020) - Chai, Fanchao; Wang, Guohui; Liu, Feng; Jiang, Danfeng; Yao, Chuqing; Xu, Tianhan; Dai, Yaodong
Abstract: Flame-retardant neutron shielding materials were synthesized based on ethylene-vinyl acetate (EVA) copolymer and with multi-walled carbon nanotubes (CNTs), boron carbide (B4 C), zinc borate (ZB) as fillers. With the increase of filler content, the tensile strength of the composite increased primarily and then decreased, and the elongation at break continued to decrease. CNTs and ZB formed a synergistic flame-retardant system. The surface-modified CNTs improved the mechanical properties, thermodynamic properties, and flame retardancy of the composites. With the increase of the CNTs content, the flame-retardant properties of composites increased first and then remained stable. Electron beam (EB) radiation changed the mechanical properties, flame retardant properties and thermodynamic properties of the composites. Taking an Am–Be neutron source as the radiation source, the thermal neutron transmittance of 2 mm sample was 50.72%. Highlights: Carbon nanotubes (CNTs) can be surface modified by silane coupling agent (KH-550). The surface-modified carbon nanotubes have improved dispersion in composites. Electron beam irradiation and CNTs improve multiple properties of composites. Zinc borate and CNTs form a synergistic flame-retardant system.